2010
DOI: 10.1093/annonc/mdq453
|View full text |Cite
|
Sign up to set email alerts
|

Optimal treatment for recurrent/metastatic head and neck cancer

Abstract: While a large proportion of patients presenting with stage I and II squamous cell carcinoma of the head and neck (SCCHN) will remain disease free after single modality treatment, the majority of patients presenting in a more advanced disease stage and very often treated with a form of combined modality treatment, will eventually relapse, either locoregionally only, at distant sites only or both. A few patients with a locoregional recurrence can be salvaged by surgery or reirradiation. However, most patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
242
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(254 citation statements)
references
References 64 publications
4
242
0
8
Order By: Relevance
“…Treatment options for metastatic disease include supportive care, single agent or a chemotherapy combination with or without targeted agents. 94 Pronostic factors of long-term survivors in metastatic SCCHN patients treated with pratinum-based chemotherapy were identified in the E1395 and E1393 randomized trials of the Eastern Cooperative Oncology Group (ECOG) and include: tumor cell differentiation, ECOG performance status (PS), weight loss, location of the primary tumor and prior radiotherapy. 95 The EXTREME trial showed that the combination of platinum-5Fluorouracil and cetuximab as first-line treatment in SSCHN improved OS, PFS and response rate with no decreased quality of life compared to the same schedule without the monoclonal antibody.…”
Section: Metastatic or Recurrent Disease (Stage Ivc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment options for metastatic disease include supportive care, single agent or a chemotherapy combination with or without targeted agents. 94 Pronostic factors of long-term survivors in metastatic SCCHN patients treated with pratinum-based chemotherapy were identified in the E1395 and E1393 randomized trials of the Eastern Cooperative Oncology Group (ECOG) and include: tumor cell differentiation, ECOG performance status (PS), weight loss, location of the primary tumor and prior radiotherapy. 95 The EXTREME trial showed that the combination of platinum-5Fluorouracil and cetuximab as first-line treatment in SSCHN improved OS, PFS and response rate with no decreased quality of life compared to the same schedule without the monoclonal antibody.…”
Section: Metastatic or Recurrent Disease (Stage Ivc)mentioning
confidence: 99%
“…Classical drugs as methotrexate, cisplatin, 5-fluorouracil (5-FU) and bleomyin have shown responses of short duration (3-5 months) and 15-30% tumor reduction. 94 Of the more recent agents, taxanes (docetaxel and paclitaxel) improved response rates up to 43% in platinum resistant patients. 99 Furthermore, Afatinib is an irreversible ERBB family blocker with significant results in the second-line setting.…”
Section: Metastatic or Recurrent Disease (Stage Ivc)mentioning
confidence: 99%
“…However, multimodality approaches are not often enough. Locoregional recurrence or distant methastasis (R/M-HNSCC) develop in significant number of the patients [1,3,8].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of EGFR is related to poor prognostic factor in HNSCC [3,10]. Recently, this situation is used in the treatment as EGFR targeting strategies for HNSCC; monoclonal antibodies and tyrosine kinase inhibitors [1,10,11]. The best studied monoclonal antibody for HNSCC is cetuximab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation